Pengaruh Penggunaan Berbagai Koagulan Kimia Pada Limbah Cair Kelapa Sawit (Elaeis guineensis Jacq.) Terhadap Penurunan Beban Pencemar - Imam Fatoni; Rijadi Subiantoro; Maryanti Maryanti (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Oil palm (Elaeis guineensis Jacq.) Is a type of plantation that is Indonesia's mainstay commodity with rapid development. Palm oil industry wastewater comes from a variety of palm oil processing processes that contain high organic and inorganic materials. The resulting waste must be controlled and treated so that it does not pose a threat to the palm oil industry because it can pollute the environment and sources of disease. One method of processing palm oil liquid waste that can be used is coagulation. The coagulation process requires a coagulant, the coagulant used is aluminum sulfate, ferrous sulfate, ferric chloride. This study aims to obtain the type and dose of chemical coagulants that are effective in handling palm oil industry liquid waste in anaerobic ponds and determine the reduction of pollutant variables (COD, TSS, Turbdity, color, and pH changes) due to the treatment of coagulant treatment. This study used a Randomized Group Design (RBD) with 10 levels of treatment consisting of B0 (Non-coagulant), B1 (Al2 (SO4)3 1 g/L), B2 (Al2 (SO4)3 1,5 g/L), B3 (Al2 (SO4)3 2 g/L), B4 (FeSO47H2O 1 g/L), B5 (FeSO47H2O 1,5 g/L), B6 (FeSO47H2O 2 g/L), B7 (FeCl36H2O 1 g/L), B8 (FeCl36H2O 1,5 g/L), B9 (FeCl36H2O 1 g/L). Data were analyzed by analysis of variance (ANOVA) and a 5% LSD test. The results obtained are ferric chloride being the best coagulant to reduce polluted parameters in palm oil liquid waste and Ferri chloride 2 g/L is the best treatment for reducing pollutant parameters of COD, TSS, Turbidity, and Color. Whereas the best pH reduction in aluminum sulfate 1 g/L coagulant.